2020
DOI: 10.23887/jpi-undiksha.v9i4.27390
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Project-Based Learning Model on Students’ Resilience During the Pandemic Covid-19

Abstract: This research is motivated by a change in the implementation of learning that is usually faceto-face in the classroom to learning through online due to the pandemic covid-19. Therefore this study was conducted aiming to analyze the effect of online-based project based learning learning model on the resilience of students during the pandemic Covid-19. The research method used was preexperimental with the design of one group pretest-posttest. The research population was consisting of four classes with a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
(21 reference statements)
0
15
0
2
Order By: Relevance
“…Resilience is the ability to rise from adversity [12]. In the educational context, studies have shown that resilience affects students' psychological well-being and positive behaviors during the COVID-19 pandemic [12][13][14][15]. Therefore, in this study, resilience, a variable studied in positive psychology, is set as a moderated mediation variable, as research shows that students with strong resilience tend to cope with stressful situations more actively.…”
Section: Introductionmentioning
confidence: 98%
“…Resilience is the ability to rise from adversity [12]. In the educational context, studies have shown that resilience affects students' psychological well-being and positive behaviors during the COVID-19 pandemic [12][13][14][15]. Therefore, in this study, resilience, a variable studied in positive psychology, is set as a moderated mediation variable, as research shows that students with strong resilience tend to cope with stressful situations more actively.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, it also increases intelligence and creativity in solving problems (Nurrohmi et al, 2017). Similarly, positive collaboration helps individuals or groups to achieve goals and shape learners to be tolerant, open-minded toward others' ideas, attitudes, and behaviors (Awaliyah et al, 2016;Dani et al, 2020;Pratiwi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Rahayu & Fauzi (2020), there are several stages of implementation carried out in applying the project based learning during pandemic situation, are: 1) the lectures gives a challenging statement related to the technological developments in the world of education related to technological development in education; 2) project planning, students and lecturer together make project plans; 3) compile schedules for project development, schedules that are made together are also arranged and mutually agreed; 4) supervise the preparation of the project, this process is carried out until the project can be completed through the use of Google Classroom; 5) the resulting project appraisal, the project appraisal is carried out after the student's project is completed with the agreed assessment indicators; 6) evaluation, at this stage students are given an evaluation with an observation sheet to measure students' abilities.…”
Section: How the English Teacher Implemented Project-based Learning D...mentioning
confidence: 99%